2023
DOI: 10.16926/par.2023.11.10
|View full text |Cite
|
Sign up to set email alerts
|

Physical fitness of students in Indonesian during the COVID-19 period: Physical activity, body mass index, and socioeconomic status

Abstract: The coronavirus disease (COVID-19) pandemic has caused the physical education learning process to switch to online methods. Conditions such as this do not result in optimal Physical Activity (PA) (sports activity) carried out by students, which has an impact on their Physical Fitness (PF). With regard to PF, Body Mass Index (BMI) and socioeconomic status (SES) during the COVID-19 period also need to be investigated. Therefore, this study aimed to analyze the effects of PA, BMI, and SES on students' PF during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…This tool is an innovation in sports technology for collecting data in sports involving hand-eye coordination (such as volleyball, badminton, tennis, basketball, hockey, martial arts and other sports where hands are dominant). This includes game sports in physical education as well (Firdaus et al, 2023;Umar, Alnedral, Ihsan, Mario, & Mardesia, 2023;Welis, Yendrizal, Darni, & Mario, 2023). Previous studies reported that technology in the sports sector is a complex system for collecting and processing large amounts of data (Camomilla, Bergamini, Fantozzi, & Vannozzi, 2018;Ratten, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This tool is an innovation in sports technology for collecting data in sports involving hand-eye coordination (such as volleyball, badminton, tennis, basketball, hockey, martial arts and other sports where hands are dominant). This includes game sports in physical education as well (Firdaus et al, 2023;Umar, Alnedral, Ihsan, Mario, & Mardesia, 2023;Welis, Yendrizal, Darni, & Mario, 2023). Previous studies reported that technology in the sports sector is a complex system for collecting and processing large amounts of data (Camomilla, Bergamini, Fantozzi, & Vannozzi, 2018;Ratten, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Protein supplementation will only produce muscle strength with carefully planned, structured, and prolonged weight training. According to previous research, effective sports training must be planned and programmed (Antara et al, 2023;Firdaus et al, 2023;Umar et al, 2023;Welis et al, 2023). In weight training, it is important to know the following: intensity and volume of training, sequence of exercises, number of repetitions, sets, tempo of movement, rest time between sets, and type of exercise (Ralston et al, 2018), Weight training with short (60 seconds or less) and long (more than 60 seconds) rest intervals can help in training muscle strength (Grgic et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…FMS also lays the groundwork for complex movement patterns, including object control skills (like throwing, catching, kicking), locomotor skills (like running, jumping), and stability (involving static and dynamic balance) [7,8]. Each of these components is equally important for improving motor skills [9,10], both during and outside the physical education schedule [11,12]. FMS and physical activity are also frequent focuses of researchers [13][14][15][16], and as a correlation between BMI and fitness [17].…”
Section: Introductionmentioning
confidence: 99%